56*56+33*33=x*x

Simple and best practice solution for 56*56+33*33=x*x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56*56+33*33=x*x equation:


Simplifying
56 * 56 + 33 * 33 = x * x

Multiply 56 * 56
3136 + 33 * 33 = x * x

Multiply 33 * 33
3136 + 1089 = x * x

Combine like terms: 3136 + 1089 = 4225
4225 = x * x

Multiply x * x
4225 = x2

Solving
4225 = x2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x2' to each side of the equation.
4225 + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
4225 + -1x2 = 0

Add '-4225' to each side of the equation.
4225 + -4225 + -1x2 = 0 + -4225

Combine like terms: 4225 + -4225 = 0
0 + -1x2 = 0 + -4225
-1x2 = 0 + -4225

Combine like terms: 0 + -4225 = -4225
-1x2 = -4225

Divide each side by '-1'.
x2 = 4225

Simplifying
x2 = 4225

Take the square root of each side:
x = {-65, 65}

See similar equations:

| 9-12=3n | | 9m+5n-5m+8n= | | 12x-9y+3= | | 2x-x^3+5=3 | | 0.3x+0.2(x-7)=8 | | 6x-3=9# | | 2X-6Y=2 | | 9y=x | | 0.5x^4+1=1.25x^3-1 | | 9x+25=4x | | -6x+5=2-3-5x+x | | x^4+x-2=0 | | 4m-5=m-5 | | 7+7x=6x-9 | | 11x+33=5x-129 | | x-(0.03x)=29 | | 6t^2-5t-4=0 | | -14=x+12/-6 | | 3x+8=89-6 | | 2/3w=8 | | 3(x+7)2+17=25 | | 1/2x=3 | | p=25 | | -3/4(12x-8)=-18 | | 20-4x=5x-35 | | a^2+2a+8=0 | | x-6=42 | | 4x+y=-20 | | 2p-1=3y+11 | | 29-H=207 | | 9x-4x+32=6x-21 | | 33=0+3y |

Equations solver categories